Preparing for and managing change: climate adaptation for biodiversity and ecosystems. Issue 9 (1st November 2013) - Stein, Bruce A; Staudt, Amanda; Cross, Molly S; Dubois, Natalie S; Enquist, Carolyn; Griffis, Roger; Hansen, Lara J; Hellmann, Jessica J; Lawler, Joshua J; Nelson, Erik J; Pairis, Amber
Abstract : The emerging field of climate‐change adaptation has experienced a dramatic increase in attention as the impacts of climate change on biodiversity and ecosystems have become more evident. Preparing for and addressing these changes are now prominent themes in conservation and natural resource policy and practice. Adaptation increasingly is viewed as a way of managing change, rather than just maintaining existing conditions. There is also increasing recognition of the need not only to adjust management strategies in light of climate shifts, but to reassess and, as needed, modify underlying conservation goals. Major advances in the development of climate‐adaptation principles, strategies, and planning processes have occurred over the past few years, although implementation of adaptation plans continues to lag. With ecosystems expected to undergo continuing climate‐mediated changes for years to come, adaptation can best be thought of as an ongoing process, rather than as a fixed endpoint.